Niger : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for Waiver and Modification of Performance Criteria; Staff Report; Staff Statement and Supplements; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Niger. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
Niger's Fourth Review Under the Poverty Reduction and Growth Facility and Request for Waiver and Modification of Performance Criteria are examined. Economic growth in 2006 has been satisfactory at 4.8 percent, owing to a good harvest for the second year in a row, and strong mining, telecommunications, and construction activities. Inflation has been low, and food security improved, partly because of continued donor support. The fiscal deficit in 2006 has been smaller than programmed because of underspending and exceptional mining receipts.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet